Motivation Factors of HIV Service Officers to Get SPM HIV Achievements in Sumenep District - Ratna Wardani; Mohammad Agus Suryadinata (Journal for Quality in Public Health, 2022)
The purpose of this study was to analyze the determinants of motivation for HIV service to get SPM achievements of the HIV section in Sumenep district. The population in this reseach are all HIV/AIDS service officers in Sumenep District with a total of 120 respondents. The number of samples taken were some health workers throughout the Sumenep District Health Center based on the Isaac & Michael Sample Determination Table which amounted to 102 respondents. Data collection was carried out by distributing questionnaires. The data analysis method uses multiple linear regression and data processing is used by SPSS 18. The results of hypothesis research show that the reward has a positive and significant effect on motivation, so it can be interpreted that the better the award, the higher the work motivation. Leadership supervision is not statistically significant p (0.87) > (0.05), so that leadership supervision has no effect on the motivation of HIV service workers. The period of service is statistically significant p(0.046) < (0.05), so it can be interpreted that the longer period of service, the higher the level of employee motivation. The leadership style variable on motivation shows that the p-value is 0.000 < (0.05) then H0 is rejected and H1 is accepted so it is concluded that there is a positive influence between leadership style on the motivation of HIV service workers in Sumenep District.